DEVELOPING COMMUNITY POTENTIAL THROUGH MSME EMPOWERMENT, HEALTH, AND INCREASING AWARENESS OF RELIGIOUS EDUCATION, IN CIAMPEA DISTRICT - Yusuf, Ujang Andi; Nurdin, Irfan Bahar; Hafizin, Hafizin (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service Activities (PKM) are activities carried out by the STAI Al-Hidayah Bogor Lecturer Team which aims to foster and develop the social life of religion in the community of Benteng Village, assisting the local government in accelerating the process of community development, especially in the social field of religion in Ciampea District. These activities include Al-Fatihah dauroh training, funeral management training, Islamic studies, da'wah safaris, and Al-Quran teaching at several TPQ locations. Then in the health sector, namely with the cupping program and free medical health services. In the social field, including training in grape cultivation, community service, blessing Fridays, compensation for orphans and poor people, and the distribution of IQRO and Qur'an books. This activity went well because it received full support from the community, and is expected to be a controversy and inspiration for the surrounding community